Mindfulness-Based Cognitive Therapy in Major Depressive Disorder: A Study Protocol of a Randomized Control Trial and a Case–Control Study With Electroencephalogram - Zhang, Tianran; Wang, Lanlan; Bai, Yanle; Zhao, Wenqing; Wu, Yanru; Jiang, Wenhui; Fan, Qing; Qiu, Jianyin (Frontiers in Psychiatry, 2021)
Background: This report presents the study protocol of a randomized control trial to explore the efficacy of mindfulness-based cognitive therapy for a major depressive disorder(MMD) and a case-control study to find the change of electroencephalogram between MMD and normal controls. Design: There will be 70 Chinese MMD to be randomized to the MBCT group or medication group, half of the cases will receive usual medication treatment with the serotonin reuptake inhibitors (SSRIs) and half of the participants will receive MBCT added to the usual medication treatment. All of the participants including 70 MMD cases and 35 matched normal controls will be tested by a range of scales and EEG at baseline (week 0), mid-intervention (week 2, 4, and 6), post-intervention (week 8), and 6-month follow-up (weeks 12, 20, and 32). Discussion: The study will have a great impact on the treatment of depression and the development of the research on MBCT treatment mechanism. Trial registration: NCT03558256. Registered 13 June 2018 - Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT03558256